Grand Challenges for Archaeology. Issue 1 (January 2014) - Kintigh, Keith W.; Altschul, Jeffrey H.; Beaudry, Mary C.; Drennan, Robert D.; Kinzig, Ann P.; Kohler, Timothy A.; Limp, W. Fredrick; Maschner, Herbert D. G.; Michener, William K.; Pauketat, Timothy R.; Peregrine, Peter; Sabloff, Jeremy A.; et al.
Abstract: This article represents a systematic effort to answer the question, What are archaeology's most important scientific challenges? Starting with a crowd-sourced query directed broadly to the professional community of archaeologists, the authors augmented, prioritized, and refined the responses during a two-day workshop focused specifically on this question. The resulting 25 "grand challenges" focus on dynamic cultural processes and the operation of coupled human and natural systems. We organize these challenges into five topics: (1) emergence, communities, and complexity; (2) resilience, persistence, transformation, and collapse; (3) movement, mobility, and migration; (4) cognition, behavior, and identity; and (5) human-environment interactions. A discussion and a brief list of references accompany each question. An important goal in identifying these challenges is to inform decisions on infrastructure investments for archaeology. Our premise is that the highest priority investments should enable us to address the most important questions. Addressing many of these challenges will require both sophisticated modeling and large-scale synthetic research that are only now becoming possible. Although new archaeological fieldwork will be essential, the greatest pay off will derive from investments that provide sophisticated research access to the explosion in systematically collected archaeological data that has occurred over the last several decades.